Factors affecting the preparation of the construction work programme - Mohamad, Mardiana (2016)
Work programme can be valuable management tool that allows the contractor to use resources efficiently and provides advance notice of situations that may cause the project to be delayed. It can also be an important tool for evaluation and proving delay claims. A previous study revealed that poor factual evidence and flaws in claim such as presenting a good and proper work programme are the principal facts leading to delays construction claims. Therefore, the objectives of this research are (1) To identify the factors that affecting the preparation of better construction work programme; and (2) To determine the approaches that can improve in preparing a better construction work programme. Comprehensive literature review has been conducted to gather the information on the factors affecting the preparation of construction work schedule followed by conducting structured interview session with the project personnel who has been working in the industry for 20 years and more as a main tool to gain data to establish the affecting factors. The data attained were analyzed these factors were divided into four (4) main categories which were project specific factors, project management, working condition and external environment related factors. Hence, all respondent are in their opinion that complexity, size, type, nature of the construction project, identifying the critical activities, good relationship, good coordination, good leadership as well as scope of nature of the work are the affecting factors in preparing the construction work programme. In conclusion, the study also identified recommendations that can be used by the project participants in order to prepare effective and good construction work schedule in the local construction industry.